Double-sulfur-vacancy SV-Bi2S3 / SV-ZnIn2S4 heterojunction photocatalyst as well as preparation method and application thereof

By designing the SV-Bi2S3/SV-ZnIn2S4 heterojunction photocatalyst with disulfide vacancies, the problem of short photogenerated carrier lifetime in the photocatalyst is solved, and efficient degradation of chloroquine phosphate and the structural stability and recycling ability of the catalyst are achieved.

CN119524878AActive Publication Date: 2025-02-28EAST CHINA NORMAL UNIV

Patent Information

Application Number
CN202411725853.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-28
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The lifespan of photogenerated carriers in existing photocatalytic reactions is short, resulting in a decrease in the number of effective carriers and reducing the photocatalytic efficiency.

Method used

A disulfide vacancies SV-Bi2S3/SV-ZnIn2S4 heterojunction photocatalyst is designed to promote the separation and transfer of photogenerated carriers by composited with other materials and constructing special structures, thereby improving the stability and photocatalytic performance of the catalyst.

Benefits of technology

The efficient degradation of chloroquine phosphate is achieved, with a degradation efficiency of 99.3%, and the catalyst has good structural stability and recycling capabilities, reducing material consumption and waste generation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524878A_ABST
    Figure CN119524878A_ABST
Patent Text Reader

Abstract

The invention discloses a double sulfur vacancy SV-Bi2S3 / SV-ZnIn2S4 heterojunction photocatalyst as well as a preparation method and application of the double sulfur vacancy SV-Bi2S3 / SV-ZnIn2S4 heterojunction photocatalyst. According to the double-sulfur-vacancy SV-Bi2S3 / SV-ZnIn2S4 composite photocatalyst, the existence of the sulfur vacancy in a composite material is proved through electron paramagnetic resonance. In addition, a scanning electron microscope, X-ray diffraction and Fourier infrared analysis show that the results show that the composite materials interact with one another and have tight interface contact. In addition, the double-sulfur-vacancy SV-Bi2S3 / SV-ZnIn2S4 composite photocatalyst prepared by the preparation method disclosed by the invention has the characteristics of good structural stability and recyclability, so that the treatment cost is greatly reduced. Meanwhile, the catalyst is low in cost, chloroquine phosphate in the wastewater can be quickly decomposed and converted, the wastewater treatment efficiency is greatly improved, and the requirement of large-scale industrial application is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of photocatalysis technology, and in particular relates to a SV-Bi2S3 / SV-ZnIn2S4 heterojunction photocatalyst with double sulfur vacancies, a preparation method and an application thereof. Background Art

[0002] As a common antiviral drug, chloroquine phosphate has a concentration of 110 ng / L-33 μg / L in wastewater (Environ. Sci. Technol. 2023, 57, 7913−7923). Its residue in water bodies can have toxic effects on aquatic organisms, affecting their growth, reproduction and survival, and destroying the balance of aquatic ecosystems. In recent years, photodegradation catalytic materials can decompose them into harmless water, carbon dioxide and other small molecules. Under light conditions, the photocatalytic reaction can be started quickly, and the degradation of pollutants can be achieved in a short time, which greatly improves the treatment efficiency and saves treatment time and cost. Therefore, designing new photocatalytic materials with high catalytic activity, stable structure, and the ability to quickly produce a large number of free radicals is still a hot topic in current research.

[0003] The band gap of Bi2S3 is about 1.8 eV, which can effectively absorb visible light and even has a certain absorption capacity in the near-infrared region. This allows it to use the more abundant visible light part of solar energy for photocatalytic reactions, improve the utilization rate of solar energy, and has great potential in the field of photocatalysis. In practical applications, the photogenerated electrons and holes of Bi2S3 are easy to recombine, which will lead to a shorter lifetime of photogenerated carriers and a reduction in the number of effective carriers involved in the photocatalytic reaction, thereby reducing the photocatalytic efficiency. In order to overcome this problem, it is usually necessary to compound Bi2S3 with other materials or construct a special structure to promote the separation of photogenerated carriers and improve the stability of the catalyst.

[0004] ZnIn2S4 can maintain the stability of structure and performance to a certain extent, which is conducive to its long-term use in practical applications. Its bandgap is between 2.06 and 2.85 eV and can absorb visible light. Although ZnIn2S4 has certain photocatalytic activity, its quantum efficiency is still low compared with the ideal high-efficiency photocatalyst, that is, the efficiency of converting absorbed photons into chemical energy is not high, and it needs to be further improved to meet the needs of practical applications. Its performance can be regulated by compounding with other materials, defects, doping, etc. For example, forming a heterojunction with other semiconductor materials can improve the separation and transfer efficiency of photogenerated carriers and improve photocatalytic performance. Summary of the invention

[0005] The purpose of the present invention is to provide a SV-Bi2S3 / SV-ZnIn2S4 heterojunction photocatalyst with disulfide vacancies for photodegrading chloroquine phosphate and a preparation method thereof, which has the ability to degrade chloroquine phosphate and has good structural stability and recycling. As long as it is under light conditions, its catalytic activity can be maintained, reducing material consumption and waste generation, and meeting the requirements of sustainable development.

[0006] The specific technical solution for achieving the purpose of the present invention is: A method for preparing a double sulfur vacancy SV-Bi2S3 / SV-ZnIn2S4 heterojunction photocatalyst comprises the following steps: Step 1: Preparation of SV-Bi2S3 solution Disperse polyvinyl pyrrolidone and thiourea in ethylene glycol (EG), and continuously stir at 65°C to obtain solution A. Subsequently, add 0.1 mol / L bismuth nitrate solution B (bismuth nitrate is also dissolved in ethylene glycol, marked as solution B) to the solution A, and the amount of solution B added is 1 / 4 of the volume of solution A. After the addition is completed, continue stirring for 30-60 min, and after mixing, mark it as solution C, which is SV-Bi2S3 solution; wherein the molar ratio of polyvinyl pyrrolidone, thiourea and ethylene glycol is 1-8:1-6:2-15; Then, the mixed solution C was transferred to a polytetrafluoroethylene-lined autoclave and maintained at 120-140 °C for 6-10 h. After the reaction was completed, the obtained black precipitate was collected by centrifugation, thoroughly washed with deionized water and ethanol, and then vacuum dried at 60 °C overnight to obtain SV-Bi2S3. Step 2: Preparation of SV-ZnIn2S4 The synthesis of SV-ZnIn2S4 powder was achieved by a one-step hydrothermal method. Specifically, zinc chloride, indium chloride tetrahydrate and thioacetamide were dissolved in ethylene glycol, and then the solution was transferred to a polytetrafluoroethylene-lined stainless steel autoclave and kept at 120-160°C for 10-12 h; after cooling to room temperature, the solution was washed with ethanol and deionized water to remove any unreacted precursors, and then vacuum dried at 60°C to obtain a light yellow SV-ZnIn2S4 powder; wherein the molar ratio of zinc chloride, indium chloride tetrahydrate, thioacetamide and ethylene glycol was 0.5-1.5:1-2:2-10:5-15; Step 3: Preparation of SV-Bi2S3 / SV-ZnIn2S4 heterojunction photocatalyst Weigh the SV-ZnIn2S4 prepared in step 2 and place it in a polytetrafluoroethylene-lined high-pressure reactor, pour the solution C in step 1, stir for 1-2 h, tighten the reactor, and heat it in an electric constant temperature blast drying oven, the reaction temperature is 120-160°C, and the reaction time is 12-18 h; cool it naturally to room temperature, open the reactor, and recover the solid powder by centrifugal washing at a speed of 8000-10000 rpm and a centrifugal time of 10-20 min. Wash it with deionized water and ethanol for 3-5 times respectively, and finally place it in a vacuum drying oven at a drying temperature of 60-80°C and a drying time of 12-18 h, and grind it; obtain the disulfide vacancy SV-Bi2S3 / SV-ZnIn2S4 heterojunction photocatalyst; wherein the mass volume ratio of the SV-ZnIn2S4 to the solution C is 0.1-0.8g:10-30mL.

[0007] A double sulfur vacancy SV-Bi2S3 / SV-ZnIn2S4 heterojunction photocatalyst prepared based on the above method can detect the presence of double sulfur vacancies through an EPR spectrometer; scanning electron microscopy shows that the lily-shaped SV-Bi2S3 with double sulfur vacancies and the hydrangea-shaped SV-ZnIn2S4 are tightly combined.

[0008] A kind of application of the described double sulfur vacancy SV-Bi2S3 / SV-ZnIn2S4 heterojunction photocatalyst in degrading chloroquine phosphate in wastewater; its application process specifically comprises: placing the described catalyst in chloroquine phosphate wastewater with a concentration of 5-50 mg / L, adsorbing in the dark for 30-90 min under stirring, and after reaching adsorption equilibrium, turning on the white light LED with a power of 10-80 W for irradiation, and the irradiation time is 5-90 min; the described double sulfur vacancy SV-Bi2S3 / SV-ZnIn2S4 heterojunction photocatalyst generates a large number of free radicals to attack the chloroquine phosphate matrix to promote cracking, and the photodegradation efficiency reaches 72.4-99.3% after 60 minutes of illumination; wherein, the mass of the described photocatalyst: the volume of the wastewater is 5-200 mg: 5-200 ml.

[0009] The present invention has the following advantages: 1) The SV-Bi2S3 / SV-ZnIn2S4 heterojunction photocatalyst prepared in the present invention can achieve a maximum degradation efficiency of 99.3% for CQ in 60 min.

[0010] 2) The introduction of sulfur vacancies improves the adsorption and degradation efficiency of CQ on SV-Bi2S3 / SV-ZnIn2S4 heterojunction photocatalysts.

[0011] 3) Compared with the original SV-Bi2S3 and SV-ZnIn2S4, the prepared SV-Bi2S3 / SV-ZnIn2S4 composite photocatalyst can effectively heterogeneous electron / hole recombination, accelerate interfacial electron transfer and thus improve the photocatalytic efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 Scanning electron microscope images of SV-Bi2S3, SV-ZnIn2S4 and SV-BZI-50 prepared in Example 3 of the present invention; Figure 2 This is a transmission electron microscopy image of SV-BZI-50 prepared in Example 3 of the present invention; Figure 3 The electron paramagnetic resonance images of sulfur vacancies of SV-Bi2S3, SV-ZnIn2S4 and SV-BZI-50 prepared in Example 3 of the present invention; Figure 4 XRD patterns of SV-Bi2S3, SV-ZnIn2S4 and SV-BZI-50 prepared in Example 3 of the present invention; Figure 5 FT-IR images of SV-Bi2S3, SV-ZnIn2S4 and SV-BZI-50 prepared in Example 3 of the present invention; Figure 6 This is a graph showing the degradation performance of the SV-Bi2S3, SV-ZnIn2S4 and SV-BZI-X series composite photocatalysts of the present invention; Figure 7 The cycle performance diagram of SV-BZI-50 prepared in Example 3 of the present invention and the XRD diagram, FT-IR and SEM diagram before and after five cycle tests; Figure 8 The capture experiment diagram of SV-BZI-50 prepared in Example 3 of the present invention shows the electron paramagnetic resonance diagram of different types of free radicals; Fig. 9 This is a schematic diagram of the degradation pathway of CQ by SV-BZI-50 prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0013] The present invention is further described in conjunction with the accompanying drawings. All reagents used in the following examples are conventional reagents with analytical purity and no further purification is required before use; the relevant preparation methods and detection methods are conventional methods. Example

[0014] (1) The synthesis of SV-ZnIn2S4 powder was achieved by a one-step hydrothermal method. Specifically, zinc chloride, indium chloride tetrahydrate, and thioacetamide in a molar ratio of 1:1:2 were dissolved in 20 mL of ethylene glycol, and the solution was then transferred to a polytetrafluoroethylene-lined stainless steel autoclave and kept at 160 °C for 12 h. After cooling to room temperature, the solution was washed with ethanol and deionized water to remove any unreacted precursors, and light yellow SV-ZnIn2S4 powder was obtained after vacuum drying at 60 °C.

[0015] (2) Synthesis of SV-Bi2S3 / SV-ZnIn2S4 heterojunction photocatalyst Disperse polyvinyl pyrrolidone and thiourea in ethylene glycol (EG) and stir continuously at 65°C to obtain solution A. Subsequently, add 0.1 mol / L bismuth nitrate solution B (bismuth nitrate is also dissolved in ethylene glycol, marked as solution B) to solution A, and the amount of solution B added is 1 / 4 of the volume of solution A. After the addition is completed, continue stirring for 30 min, and mark it as solution C after mixing. Weigh 0.10 g SV-ZnIn2S4 and place it in the polytetrafluoroethylene-lined high-pressure reactor of step 1, pour in 30 mL solution C and stir for 1 h. Tighten the reactor and heat it with an electric constant temperature blast drying oven. The reaction temperature is 140°C and the reaction time is 12 h. Cool it naturally to room temperature, open the reactor, and recover the solid powder by centrifugal washing at a speed of 8000 rpm and a centrifugal time of 10 min. Wash it with deionized water and ethanol for 3 times respectively, and finally put it in a vacuum drying oven at a drying temperature of 60°C and a drying time of 12 h, grinding; the double sulfur vacancy SV-Bi2S3 / SV-ZnIn2S4 heterojunction photocatalyst was obtained, recorded as SV-BZS-10. Example

[0016] (1) The synthesis of SV-ZnIn2S4 powder was achieved by a one-step hydrothermal method. Specifically, zinc chloride, indium chloride tetrahydrate, and thioacetamide in a molar mass ratio of 1:1:2 were dissolved in 20 m ethylene glycol, and the solution was then transferred to a polytetrafluoroethylene-lined stainless steel autoclave and kept at 160 °C for 12 h. After cooling to room temperature, the solution was washed with ethanol and deionized water to remove any unreacted precursors, and light yellow SV-ZnIn2S4 powder was obtained after vacuum drying at 60 °C.

[0017] (2) Synthesis of SV-Bi2S3 / SV-ZnIn2S4 heterojunction photocatalyst Disperse polyvinyl pyrrolidone and thiourea in ethylene glycol (EG) and stir continuously at 65°C to obtain solution A. Subsequently, add 0.1 mol / L bismuth nitrate solution B (bismuth nitrate is also dissolved in ethylene glycol, marked as solution B) to solution A, and the amount of solution B added is 1 / 4 of the volume of solution A. After the addition is completed, continue stirring for 30 min, and mark it as solution C after mixing. Weigh 0.30 g SV-ZnIn2S4 and place it in the polytetrafluoroethylene-lined high-pressure reactor of step 1, pour in 30 mL solution C and stir for 1 h. Tighten the reactor and heat it with an electric constant temperature blast drying oven. The reaction temperature is 140°C and the reaction time is 12 h. Naturally cool to room temperature, open the reactor, and recover the solid powder by centrifugal washing at a rotation speed of 8000. rpm, centrifugal time 10min, washed with deionized water and ethanol three times respectively, and finally put into a vacuum drying oven, dried at 60°C, dried for 12h, and ground; the double sulfur vacancy SV-Bi2S3 / SV-ZnIn2S4 heterojunction photocatalyst was obtained, recorded as SV-BZS-30. Example

[0018] (1) Polyvinyl pyrrolidone and thiourea were dispersed in ethylene glycol (EG) and stirred continuously at 65°C to obtain solution A. Subsequently, 0.1 mol / L bismuth nitrate solution B (bismuth nitrate was also dissolved in ethylene glycol, marked as solution B) was added dropwise to solution A. The amount of solution B added was 1 / 4 of the volume of solution A. After the addition was completed, stirring was continued for 30 min. After mixing, the solution C was marked as solution C. Then, the mixed solution C was transferred to a polytetrafluoroethylene-lined autoclave and kept at 140°C for 8 h. After the reaction was completed, the black precipitate was collected by centrifugation, thoroughly washed with deionized water and ethanol, and then vacuum dried at 60°C overnight to obtain SV-Bi2S3. The molar ratio of polyvinyl pyrrolidone, thiourea and ethylene glycol was 1:1:2.

[0019] (2) The synthesis of SV-ZnIn2S4 powder was achieved by a one-step hydrothermal method. Specifically, zinc chloride, indium chloride tetrahydrate, and thioacetamide in a molar mass ratio of 1:1:2 were dissolved in 20 mL of ethylene glycol, and the solution was then transferred to a polytetrafluoroethylene-lined stainless steel autoclave and kept at 160 °C for 12 h. After cooling to room temperature, the solution was washed with ethanol and deionized water to remove any unreacted precursors, and light yellow SV-ZnIn2S4 powder was obtained after vacuum drying at 60 °C.

[0020] (3) Synthesis of SV-Bi2S3 / SV-ZnIn2S4 heterojunction photocatalyst Weigh 0.50 g of SV-ZnIn2S4 and place it in the polytetrafluoroethylene-lined high-pressure reactor of step 1, pour in 30 mL of solution C of step 1 and stir for 1 h; tighten the reactor and heat it with an electric constant temperature forced air drying oven, the reaction temperature is 140°C, and the reaction time is 12 h; cool naturally to room temperature, open the reactor, and recover the solid powder by centrifugal washing at a speed of 8000 rpm and a centrifugal time of 10 min, wash it with deionized water and ethanol for 3 times respectively, and finally place it in a vacuum drying oven at a drying temperature of 60°C for 12 h, and grind it; the double sulfur vacancy SV-Bi2S3 / SV-ZnIn2S4 heterojunction photocatalyst is obtained, which is recorded as SV-BZS-50 heterojunction photocatalyst. Example

[0021] (1) The synthesis of SV-ZnIn2S4 powder was achieved by a one-step hydrothermal method. Specifically, zinc chloride, indium chloride tetrahydrate, and thioacetamide in a molar mass ratio of 1:1:2 were dissolved in 20 mL of ethylene glycol, and the solution was then transferred to a polytetrafluoroethylene-lined stainless steel autoclave and kept at 160 °C for 12 h. After cooling to room temperature, the solution was washed with ethanol and deionized water to remove any unreacted precursors, and light yellow SV-ZnIn2S4 powder was obtained after vacuum drying at 60 °C.

[0022] (2) Synthesis of SV-Bi2S3 / SV-ZnIn2S4 heterojunction photocatalyst Polyvinyl pyrrolidone and thiourea are dispersed in ethylene glycol (EG) and stirred continuously at 65°C to obtain solution A. Subsequently, bismuth nitrate solution B (bismuth nitrate is also dissolved in ethylene glycol, marked as solution B) with a concentration of 0.1 mol / L is added dropwise to solution A, and the amount of solution B added is 1 / 4 of the volume of solution A. After the addition is completed, stirring is continued for 30 min, and the mixture is marked as solution C. 0.70 g of SV-ZnIn2S4 is weighed and placed in a polytetrafluoroethylene-lined high-pressure reactor in step 1, and 30 mL of solution C in step 1 is poured in and stirred for 1 h. The reactor is tightened and heated in an electric constant temperature blast drying oven at a reaction temperature of 140°C and a reaction time of 12 h. The reactor is naturally cooled to room temperature, the reactor is opened, and the solid powder is recovered by centrifugal washing at a rotation speed of 8000 rpm and a centrifugal time of 10 min. The solid powder is washed 3 times with deionized water and ethanol respectively, and finally placed in a vacuum drying oven at a drying temperature of 60°C and a drying time of 12 h, grinding; the double sulfur vacancy SV-Bi2S3 / SV-ZnIn2S4 heterojunction photocatalyst was obtained, recorded as SV-BZS-70. Example

[0023] Weigh 10 mg of the photocatalyst and 15 mg / L of CQ solution, respectively, with a reaction volume of 50 ml, stir at 500 rmp / min in a photocatalytic reactor for dark adsorption for 5-60 min, and sample and test to reach adsorption equilibrium (the characteristic absorption peak of CQ is at 342 nm, and adsorption equilibrium is reached when the absorbance remains unchanged after two tests). Then, turn on the light source for 5-60 min when the light source is a white light LED. Calculate the specific photodegradation efficiency based on the experimental results of the test.

[0024] In order to prove the stability of the structure and performance of the catalyst, the catalyst was centrifugally washed 3-5 times with water and ethanol solution respectively after the experiment, and the obtained product was dried in a vacuum drying oven at 60°C for 12 h. In the cycle experiment, the above operation was repeated 5 times, which was 5 test cycles. Example

[0025] The capture experiment verified the presence of different types of photocatalytically active substances in SV-BZI-50. 1 mmol / L of capture agents, such as isopropanol, benzoquinone, silver nitrate, L-histidine, and triethanolamine, were added to the typical photocatalytic reaction solution to capture •OH, •O2−, e-, 1O2, and h+, respectively. The sampling and testing methods were consistent with the original photocatalytic reaction steps.

[0026] The characteristics of the composite photocatalyst of the present invention can be fully demonstrated by referring to the attached drawings of the present invention. Figure 1 The scanning electron microscopy of a shows that pure SV-Bi2S3 is 1 μm lily-shaped, while SV-ZnIn2S4 is 3 μm hydrangea-shaped ( Figure 1 b). After the heterojunction photocatalyst is prepared, the morphology of SV-BZI-50 is that the lily-shaped SV-Bi2S3 and the hydrangea-shaped SV-ZnIn2S4 are closely combined ( Figure 1 c), the size and morphology of the two remain unchanged, and transmission electron microscopy also confirms the successful preparation of the heterojunction catalyst ( Figure 2 ).

[0027] Figure 3 All samples prepared according to Example 3 show a Lorentzian line with a g value of 2.003, which proves the generation of sulfur vacancies, which not only provide more unsaturated sites for the formation of unpaired electrons, but also promote the photoinduced electron / hole separation.

[0028] Figure 4Fourier transform infrared spectroscopy demonstrated that SV-BZS-50 exhibited a similar spectrum to SV-Bi2S3, and it is noteworthy that the stretching vibration at 562 cm-1 was attributed to SV-ZnIn2S4, which indicated that the interaction between SV-BZS-50 and SV-Bi2S3 at their interface was complex, rather than just a simple combination.

[0029] Figure 5 X-ray diffraction shows that not only the characteristic peaks of SV-Bi2S3 and SV-ZnIn2S4 can be observed in SV-BZS-50, but also the diffraction peak intensity of SV-ZnIn2S4 in the composite sample increases slightly with the increase of SV-ZnIn2S4 content, which indicates the strong interaction between SV-Bi2S3 and SV-ZnIn2S4 and represents the successful synthesis of heterojunction catalyst.

[0030] Figure 6 The CQ photodegradation experimental results show that the CQ degradation efficiency of SV-BZI-50 can reach up to 99.3% within 60 min, which is much higher than that of SV-Bi2S3 and SV-ZnIn2S4. Figure 7 The CQ degradation rate of SV-BZI-50 in a still reached 91.6% after 5 consecutive cycles. The XRD ( Figure 7 b), FT-IR ( Figure 7 c) and SEM( Figure 7 d), proving that the crystal structure, functional groups and morphology of SV-BZI-50 remain consistent, indicating that it has no catalyst poisoning and is reusable and has good structural stability.

[0031] Trapping experiments and electron spin resonance spectroscopy were used to detect the types of reactive oxygen species produced by photocatalytic reactions. Figure 8 As shown in Figure 7a, the degradation efficiency without any capture agent is 99.3%, while the addition of AgNO3, BQ and L-histidine makes the degradation efficiency only 28.2%, 21.5% and 39.7%, respectively. It can be confirmed that the main active substances in the photodegradation of CQ by SV-BZI-50 are e-, .O2- and •OH. As shown in Figure 7b-c, no characteristic peaks of .O2- and •OH were observed under dark conditions, which proves that almost no .O2- and •OH were produced under dark conditions. However, the characteristic peaks of .O2- and •OH can be clearly observed under light conditions, indicating that more .O2- and •OH are produced under light conditions to attack CQ, thereby improving the photodegradation efficiency. In addition, the reduction of TEMPO by electrons leads to the formation of TEMPOH and causes a decrease in the intensity of the electron spin resonance spectrum. Figure 7d shows that under light conditions, the TEMPO signal is significantly reduced, which confirms that the SV-BZI-50 prepared by the constructed heterojunction can generate more electrons and has stronger reduction ability.

[0032] like Fig. 9 The initial substrate shown was ionized in the mass spectrometry positive ion mode to obtain the quasi-molecular ion [M+H]+ A of the proton adduct of the corresponding product with a m / z of 320. The possible reaction channels are as follows: 1) the Csp2-N bond connected to quinoline was cleaved to obtain product B m / z 159, which may further be deaminated to obtain product D m / z 142 or de-N-ethylated to obtain product Em m / z 131, and further de-N-ethylated to obtain product F m / z 103; 2) the Csp3-N bond was cleaved to obtain product aminochloroquinoline m / z 179 and product D m / z 142, which was further deethylated in the form of deethylene to obtain product G m / z 114, which was further deethylated in the form of deethylene to obtain product H m / z 86, and product D m / z 142 was deethylated in the form of deethane to obtain product P m / z 112, which was then oxidized and degraded to obtain product Q m / z 112. In addition, product D m / z 142 is further oxidized to obtain product I m / z 158, and its further degradation is manifested by the cleavage of C―C bond to obtain product m / z 130, and deethylation in the form of deethylene to obtain product K m / z 102 or deethylation in the form of deethane to obtain product P m / z 110. Product I m / z 158 can also be further degraded to obtain product M m / z 130, which is further deethylated in the form of deethylene to obtain product N m / z 102 or deethylation in the form of deethane to obtain product O m / z 100. It is speculated that the above product oxidation degradation performance obtains small molecular acids and finally obtains H2O, CO2, CO32-, NH4+, etc., thereby achieving complete degradation of the compound.

[0033] The above examples show that the SV-Bi2S3 / SV-ZnIn2S4 heterojunction photocatalyst with double sulfur vacancies prepared by the present invention has good cyclicity and structural stability, can efficiently treat CQ wastewater, has a simple and easy preparation process, good photocatalytic activity, and good operability in large-scale preparation. This study provides theoretical support for the design of new heteroatom defect heterojunction photocatalysts to remove new pollutants from water bodies for the protection of the ecological environment and the sustainable utilization of water resources.

Claims

1. A method for preparing a double sulfur vacancy SV-Bi2S3 / SV-ZnIn2S4 heterojunction photocatalyst, characterized in that: The method comprises the following steps: Step 1: Preparation of SV-Bi2S3 solution Dispersing polyvinyl pyrrolidone and thiourea in ethylene glycol, and continuously stirring at 65° C. to obtain solution A, then dripping bismuth nitrate solution B with a concentration of 0.1 mol / L into solution A, and the amount of solution B dripped is 1 / 4 of the volume of solution A; after the dripping is completed, stirring is continued for 30-60 min, and after mixing, it is marked as solution C, that is, SV-Bi2S3 solution; wherein the molar ratio of polyvinyl pyrrolidone, thiourea and ethylene glycol is 1-8:1-6:2-15; Step 2: Preparation of SV-ZnIn2S4 Dissolve zinc chloride, indium chloride tetrahydrate and thioacetamide in ethylene glycol, then transfer the solution to a polytetrafluoroethylene-lined stainless steel autoclave and keep it at 120-160°C for 10-12 hours; after cooling to room temperature, wash the solution with ethanol and deionized water to remove any unreacted precursors, and obtain a light yellow SV-ZnIn2S4 powder after vacuum drying at 60°C; wherein the molar ratio of zinc chloride, indium chloride tetrahydrate, thioacetamide and ethylene glycol is 0.5-1.5:1-2:2-10:5-15; Step 3: Preparation of SV-Bi2S3 / SV-ZnIn2S4 heterojunction photocatalyst Weigh the SV-ZnIn2S4 of step 2 and place it in a polytetrafluoroethylene-lined high-pressure reactor, pour the solution C of step 1, stir for 1-2 h, tighten the reactor, and heat it with an electric constant temperature blast drying oven, the reaction temperature is 120-160°C, and the reaction time is 12-18 h; cool it naturally to room temperature, open the reactor, and recover the solid powder by centrifugal washing at a speed of 8000-10000rpm and a centrifugal time of 10-20 min, wash it with deionized water and ethanol for 3-5 times respectively, and finally put it into a vacuum drying oven at a drying temperature of 60-80°C and a drying time of 12-18 h, and grind it; obtain the disulfide vacancy SV-Bi2S3 / SV-ZnIn2S4 heterojunction photocatalyst; wherein the mass volume ratio of the SV-ZnIn2S4 to the solution C is 0.1-0.8g:10-30mL.

2. A double sulfur vacancy SV-Bi2S3 / SV-ZnIn2S4 heterojunction photocatalyst prepared based on the method described in claim 1.

3. The double sulfur vacancy SV-Bi2S3 / SV-ZnIn2S4 heterojunction photocatalyst according to claim 2, characterized in that: The presence of disulfur vacancies can be detected by EPR spectrometry; scanning electron microscopy shows that the lily-shaped SV-Bi2S3 and hydrangea-shaped SV-ZnIn2S4 with disulfur vacancies are tightly combined.

4. An application of the double sulfur vacancy SV-Bi2S3 / SV-ZnIn2S4 heterojunction photocatalyst described in claim 2 in degrading chloroquine phosphate in wastewater.

5. The use according to claim 4, characterized in that: The specific process includes: placing the catalyst in chloroquine phosphate wastewater with a concentration of 5-50 mg / L, adsorbing in the dark for 30-90 min under stirring, and after reaching adsorption equilibrium, turning on a white light LED with a power of 10-80 W for irradiation for 5-90 min; the double sulfur vacancy SV-Bi2S3 / SV-ZnIn2S4 heterojunction photocatalyst generates a large number of free radicals to attack the chloroquine phosphate matrix to promote cracking, and the photodegradation efficiency reaches 72.4-99.3% after 60 min of illumination; wherein, the mass of the photocatalyst: the volume of wastewater is 5-200 mg: 5-200 ml.

Citation Information

Patent Citations

  • Preparation method of Z-type heterojunction photocatalyst containing S vacancy

    CN113856671A

  • Preparation and dual-function application of photoelectric catalyst Bi2S3-delta / Co1-xS with sulfur / cobalt anion and cation double vacancies

    CN117123239A

  • Preparation method and application of double-S-type heterojunction graphite carbon nitride / copper ferrite / sulfur zinc indium composite photocatalyst

    CN117619421A

  • ZnIn2S4 / Bi2S3 photocatalytic material synthesized by template method as well as preparation method and application of ZnIn2S4 / Bi2S3 photocatalytic material

    CN118122346A

Cited By

  • Preparation method of monatomic synergistic coordination composite photoelectric catalyst

    CN119800433A